1999
DOI: 10.4319/lo.1999.44.3_part_2.0932
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors on coral reefs: A long ‐term perspective

Abstract: Coral reefs are subject to a high frequency of recurrent biological and physical disturbances. The temporal and spatial scales of these are often large and difficult to study, so that most of our knowledge of disturbances on coral reefs comes from investigations conducted at one or a few sites, over short periods of time. We argue that studying single events in isolation can be misleading and that a longer term approach is necessary for understanding the responses of coral reef assemblages to multiple stressor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
392
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 561 publications
(400 citation statements)
references
References 45 publications
5
392
1
2
Order By: Relevance
“…Eutrophication, pollution and sedimentation were found to hamper gamete production, alter the timing of spawning and decrease the fertilization success (Gilmour, 1999;Loya et al, 2004). They were found to slow the development and metamorphosis of the larvae and decrease the survival of the coral recruits (Gilmour, 1999;Hughes and Connell, 1999;Abelson et al, 2005). Eutrophication is also known to foster the growth of potential space competitors of coral recruits (Tomascik, 1991;Dunstan and Johnson, 1998;Abelson et al, 2005), toxic cyanobacteria or macroalgae inhibiting coral larvae settlement (Kuffner and Paul, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eutrophication, pollution and sedimentation were found to hamper gamete production, alter the timing of spawning and decrease the fertilization success (Gilmour, 1999;Loya et al, 2004). They were found to slow the development and metamorphosis of the larvae and decrease the survival of the coral recruits (Gilmour, 1999;Hughes and Connell, 1999;Abelson et al, 2005). Eutrophication is also known to foster the growth of potential space competitors of coral recruits (Tomascik, 1991;Dunstan and Johnson, 1998;Abelson et al, 2005), toxic cyanobacteria or macroalgae inhibiting coral larvae settlement (Kuffner and Paul, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Overfishing could lead to a significant decimation of grazers, which control e.g. algae growth, hence controlling potential space competitor for coral recruits (Hughes and Connell, 1999). Furthermore, reef destruction through blast fishing was shown to increase the proportion and spatial extent of coral rubble, which because of its low resistance to physical dislodgement by waves and currents may provide a killing field for coral spat (Harrison and Wallace, 1990;Fox et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Physical disturbances can have lasting effects on coral communities (Hughes and Connell 1999;Bythell et al 2000), and impact studies following Hurricane Andrew revealed that disturbance was very patchy (Tilmant et al 1994;Blair et al 1994). Further, historical changes to coral communities can affect competitive interactions among benthic organisms many years after the disturbance event (Hughes 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Disease pathogens are still present (Santavy et al 2001;Aronson and Precht 2001c;Patterson et al 2002), cold-weather fronts still occur, bleaching events are increasing in frequency and intensity, hurricanes can set back reef development, and predators are continuing to take their toll on remnant populations (Knowlton, Lang, and Keller 1990;Miller 2001), especially when other stressors are also present (Hughes 1989(Hughes , 1994Knowlton 1992;Hughes and Connell 1999). Suitable substrate may also limit larval recruitment where algal populations remain high (Hughes and Tanner 2000).…”
Section: The Futurementioning
confidence: 99%